Development and validation of a basic first aid questionnaire for school children - Jamaludin, Thandar Soe Sumaiyah; Nurumal, Mohd. Said; Sanusi, Zainal Abidin; Che Hasan, Muhammad Kamil; Firdaus, Mohd Khairul Zul Hasymi; Che Abdullah, Che Azunie; Win, Kyu Kyu; Sutrisno, Resti Yulianti; Setiawan, Henri (KARYA ILHAM PUBLISHING, 2026)
Basic first aid knowledge is a critical life-saving skill that can reduce injury severity and prevent complications during emergencies. Refugee school children are particularly vulnerable due to unsafe environments and limited access to healthcare. However, there is a lack of age-appropriate, psychometrically sound instruments to assess first aid knowledge in this population. This study aimed to develop and validate a Basic First Aid Questionnaire for refugee children aged 7–15 years. The questionnaire was adapted from a previous study and underwent forward–backward translation and cultural adaptation. Content validity was assessed by an expert panel of eight specialists, with Item-level Content Validity Index (I-CVI) values ranging from 0.75 to 1.00 and a Scale-level Content Validity Index (S-CVI/Ave) of 1.00 after refinement. A pilot study involving 30 children demonstrated good internal consistency, with Cronbach’s alpha values of 0.87 and 0.85. The findings indicate that the questionnaire is a valid and reliable tool for assessing first aid knowledge, attitudes, and awareness among refugee school children, supporting the evaluation of first aid education programmes in vulnerable communities.